Military community engagement to prevent firearm-related violence: adaptation of project safe guard for service members - S. Rachel Kennedy; Jessica Buck-Atkinson; Jayna Moceri-Brooks; Megan L. Johnson; Michael D. Anestis; Makala Carrington; Justin C. Baker; Mary E. Fisher; Donald E. Nease; AnnaBelle O. Bryan; Craig J. Bryan; Marian E. Betz (BMC, 2024)
Abstract Background Suicide, especially by firearm, remains a leading cause of death in military populations in the USA. Reducing access to firearms, especially during high risk times, may help prevent suicide and other forms of violence. The purpose of this study was to adapt a promising existing lethal means safety intervention (Project Safe Guard, PSG) for cross-cutting violence prevention and peer support in active-duty service communities using community engagement methods. Methods A two-pronged community-engaged research approach was employed, including the Community Translation (CT) process that engaged 15 Service Members from one installation to help adapt PSG successfully. In addition, qualitative data was collected from 40 active-duty service members and military violence prevention specialists through in-depth interviews and focus group discussions. Results Qualitative data and CT feedback led to site-specific PSG adaptations. Participants emphasized the importance of peer-to-peer discussions and highlighted resource allocation, leadership support, and stigma on firearm ownership as potential implementation challenges. Conclusions Findings demonstrate the feasibility of community-engaged research to adapt lethal means safety interventions within military populations. PSG implementation should consider resource allocation, leadership support, and addressing stigma. This study has implications for future policies and standards for performing research on sensitive topics, particularly among military populations.